Efficient production and characterization of the novel and highly active antifungal protein AfpB from Penicillium digitatum. Issue 1 (December 2017) - Garrigues, Sandra; Gandía, Mónica; Popa, Crina; Borics, Attila; Marx, Florentine; Coca, María; Marcos, Jose; Manzanares, Paloma
Abstract Filamentous fungi encode distinct antifungal proteins (AFPs) that offer great potential to develop new antifungals. Fungi are considered immune to their own AFPs as occurs inPenicillium chrysogenum, the producer of the well-known PAF. ThePenicillium digitatum genome encodes only oneafp gene (afpB ), and the corresponding protein (AfpB) belongs to the class B phylogenetic cluster. Previous attempts to detect AfpB were not successful. In this work, immunodetection confirmed the absence of AfpB accumulation in wild type and previous recombinant constitutiveP .digitatum strains. Biotechnological production and secretion of AfpB were achieved inP .digitatum with the use of aP .chrysogenum -based expression cassette and in the yeastPichia pastoris with the α-factor signal peptide. Both strategies allowed proper protein folding, efficient production and single-step purification of AfpB from culture supernatants. AfpB showed antifungal activity higher than theP .chrysogenum PAF against the majority of the fungi tested, especially againstPenicillium species and includingP .digitatum, which was highly sensitive to the self-AfpB. Spectroscopic data suggest that native folding is not required for activity. AfpB also showed notable ability to withstand protease and thermal degradation and no haemolytic activity, making AfpB a promising candidate for the control of pathogenic fungi.